History Makers: Pirates - Yount, Lisa; Nang ChanYeema (California, USA Lucent Books, 2002)
Recounts the lives of pirates such as Henry Morgan, William Dampier, WIlliam Kidd, Edward Teach (Blackbeard), Anne Bonny, Bartholomew Robers, and Woodes Rogers.
Keywords: Adult Nonfiction